Diversification by host switching and dispersal shaped the diversity and distribution of avian malaria parasites in Amazonia. Issue 9 (23rd March 2018) - Fecchio, Alan; Bell, Jeffrey Andrew; Collins, Michael David; Farias, Izeni Pires; Trisos, Christopher Harry; Tobias, Joseph Andrew; Tkach, Vasyl Volodymyr; Weckstein, Jason David; Ricklefs, Robert Eric; Batalha‐Filho, Henrique
Abstract : Understanding how pathogens and parasites diversify through time and space is fundamental to predicting emerging infectious diseases. Here, we use biogeographic, coevolutionary and phylogenetic analyses to describe the origin, diversity, and distribution of avian malaria parasites in the most diverse avifauna on Earth. We first performed phylogenetic analyses using the mitochondrial cytochrome b (cyt b ) gene to determine relationships among parasite lineages. Then, we estimated divergence times and reconstructed ancestral areas to uncover how landscape evolution has shaped the diversification of Parahaemoproteus and Plasmodium in Amazonia. Finally, we assessed the coevolutionary patterns of diversification in this host–parasite system to determine how coevolution may have influenced the contemporary diversity of avian malaria parasites and their distribution among Amazonian birds. Biogeographic analysis of 324 haemosporidian parasite lineages recovered from 4178 individual birds provided strong evidence that these parasites readily disperse across major Amazonian rivers and this has occurred with increasing frequency over the last five million years. We also recovered many duplication events within areas of endemism in Amazonia. Cophylogenetic analyses of these blood parasites and their avian hosts support a diversification history dominated by host switching. The ability of avian malaria parasites to disperse geographically and shift among avian hosts has played a major role in their radiation and has shaped the current distribution and diversity of these parasites across Amazonia.